(untitled) - 1942 Aug. 19-; Thompson, Fred; 1953-; Meaney, Colm; Johnson, Ashley; 1983-; West, Nathan; 1978- (Chatsworth, CA, 2011)
Love and faith are put to the ultimate test in this romantic drama set against the Scopes Monkey Trial of 1925. Charles Anderson is a talented young reporter engaged to Rose, who works with him at the small-town Tennessee newspaper his late father founded. As the trial unfolds, Charles is caught up in the media circus and becomes torn between his journalistic integrity and impressing his mentor, the colorful Baltimore Sun editor, who presses him to make a story instead of report one.
Keywords: Reporters and reporting; Tennessee; Drama; Evolution; Drama; Feature films; Video recordings for the hearing impaired; Historical films; Historical films; Feature films